Compact Integrated Bluetooth UWB Antenna with Quadruple Bandnotched Characteristics - Rekha P Labade; Shankar B Deosarkar; Narayan Pisharoty (Institute of Advanced Engineering and Science, 2015)
In this paper,a compact printed dualband antenna for Bluetooth and UWB applications with WiMax(3.3-3.7 GHz), C-band satellite downlink(3.7-4.2GHz), WLAN(5.15-5.825GHz) and DSRC(5.5-5.925GHz) bandnotched characteristics is proposed and investigated. By etching two half-wavelength L-shaped slots in the radiating patch and an inverted U-shaped slot in the microstrip feedline quadruple bandnotched characteristics is obtained. Further, by embedding quarter wavelength parasitic strip at two edges of U-shaped radiating patch dualband characteristics with desired bandwidth is obtained. the proposed antenna is designed and fabricated on a FR4 substrate of dimensions 24mm X 35mm that operates over a 2.4-11GHz with S11<-10dB except over notch bands of 3.3-3.7GHz, 3.7-4.2GHz,5.15-5.625GHz and 5.625-6GHz. Directional pattern in E-plane and nearly omnidirectional pattern in H-plane are observed over a UWB band except at desired bandnotched freqencies. Less variation in group delay and pulse deformation shows good time domain characteristics. In addition, the structure exhibits stable gain over the desired band.